The Effect of Open Broadcaster Software Learning Video Media on Improving Student Learning Outcomes at MIN Kudus: Pengaruh Media Video Pembelajaran Open Broadcaster Software terhadap Peningkatkan Hasil Belajar Siswa MIN Kudus - Maylana Nurfariha; Aninditiya Sri Nugraheni (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2023)
This research is motivated by the minimal use of learning media and students' difficulties in understanding report writing material. This study aims to determine the feasibility of instructional video media with OBS that was developed and its effect on improving student learning outcomes in writing reports at MIN Kudus. Media research and development adopt the ADDIE model. The research data is based on the results of the assessment of media experts, material experts, Indonesian language teachers, and the pre-test and post-test. The results showed that the development of instructional video media with OBS consisted of analysis stages, namely analysis of competence, learning, and analysis of student characteristics. Design, namely compiling a learning video media framework, compiling a learning video media systematics, and designing an evaluation tool. Development, namely compiling materials, preparing supporting drawings, compiling drafts, and making edits for improvement. Implementation, implementing video learning media with OBS for class VI A. Evaluation, by giving pre-tests and post-tests to students of class VI D as the control class and class VI A as the experimental class. Based on the results of the expert's assessment, the video media learning material for writing reports with OBS is included in the very decent category with details of the media expert score of 90.97, the material expert score of 76.9, and the Indonesian teacher's score of 96.15. Then the experimental results show that learning video media with OBS can improve student learning outcomes in writing reports at MIN Kudus, based on the average score obtained by class VI A at the pre-test stage, namely 65.73 to 90.33 on the post-test. Abstrak Penelitian ini dilatarbelakangi oleh minimnya pemanfaatan media pembelajaran dan kesulitan siswa memahami materi menulis laporan. Penelitian ini bertujuan untuk mengetahui kelayakan media video pembelajaran dengan OBS yang dikembangkan dan pengaruhnya pada peningkatkan hasil belajar materi menulis laporan siswa MIN Kudus. Penelitian dan pengembangan media mengadopsi model ADDIE. Data penelitian berdasarkan hasil penilaian ahli media, ahli materi, guru bahasa Indonesia, dan pre-test dan post-test. Hasil penelitian menunjukkan pengembangan media video pembelajaran dengan OBS terdiri atas tahap analysis, yaitu analisis kompotensi, pembelajaran, dan analisis karakteristik siswa. Design, yaitu menyusun kerangka media video pembelajaran, menyusun sistematika media video pembelajaran, dan merancang alat evaluasi. Development, yaitu menyusun materi, menyiapkan gambar pendukung, menyusun draft, dan melakukan penyuntingan guna perbaikan. Implementation, mengimplementasikan media video pembelajaran dengan OBS kepada kelas VI A. Evaluation, dengan memberikan pre-test dan post-test kepada siswa kelas VI D sebagai kelas kontrol dan kelas VI A sebagai kelas eksperimen. Berdasarkan hasil penilaian ahli, media video pembelajaran materi menulis laporan dengan OBS termasuk dalam kategori sangat layak dengan rincian nilai ahli media 90.97, nilai ahli materi 76.9, dan nilai guru bahasa Indonesia 96.15. Kemudian hasil eksperimen menunjukkan media video pembelajaran dengan OBS dapat meningkatkan hasil belajar materi menulis laporan siswa MIN Kudus, berdasarkan rata-rata nilai yang diperoleh kelas VI A pada tahap pre-test yaitu 65.73 menjadi 90.33 pada post-test.